Exploring Names: Notes on Onomastics and Fictionality in Marcel Proust's Remembrance of Things Past - Christian Moraru (Names, 1995)
Abstract The relationships between names and the literary imagination in Marcel Proust's Remembrance of Things Past are considered. In Remembrance, names are explored and interpreted by Proust, and the very process of this “deciphering” unfolds spectacular fictional worlds. Names are endowed with a “geological” dimension which the narrator scrutinizes. Starting from the external, phonetic aspect of proper names, he projects, spins off an entire universe. Challenging basic principles of lexicography, Proust deliberately “confuses” proper names’ basic property and makes them generate rich, luxuriant fictitious worlds. Characteristically, names open the Proustian gate of imagination.